Агрегатное построение пневматических систем управления - Юдицкий С. А. Семен Абрамович; Тагаевская А. А. Агния Аркадьевна; Ефремова Т. К. Тамара Константиновна; Берендс Т. К. Татьяна Константиновна; Искра И. Р. Ирина Романовна (Москва, Энергия, 1973)
Исключено из фонда НТБ ТПУ